2014
DOI: 10.1007/s10461-014-0820-1
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Violence and Association with Decreased Drug Abstinence Among Women in Cape Town, South Africa

Abstract: Drug abuse is a contributing factor in women’s HIV risk in low-income communities in Cape Town, South Africa. This study assessed whether experiencing violence is associated with reduced drug abstinence among adult women (n = 603) participating in a randomized field trial for an HIV prevention study in Cape Town. In relation to drug abstinence at 12-month follow-up, multivariable regression models were used to assess (1) baseline partner and non-partner victimization, and (2) victimization at 12-month follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Given the cross-sectional nature of the data and evidence from our earlier studies that substance use increases risk for victimisation (Wechsberg et al, 2013), it is possible that lifetime substance use may have preceded exposure to trauma. Even if this is the case, given the negative impact of trauma exposure on women's ability to quit substance use (Reed, Myers, Novak, Browne, & Wechsberg, 2014), and our finding that almost a third of trauma-exposed pregnant women reported current substance use, efforts to mitigate the consequences of trauma exposure should include screening, brief interventions, and referral to treatment for substance use.…”
Section: Discussionmentioning
confidence: 97%
“…Given the cross-sectional nature of the data and evidence from our earlier studies that substance use increases risk for victimisation (Wechsberg et al, 2013), it is possible that lifetime substance use may have preceded exposure to trauma. Even if this is the case, given the negative impact of trauma exposure on women's ability to quit substance use (Reed, Myers, Novak, Browne, & Wechsberg, 2014), and our finding that almost a third of trauma-exposed pregnant women reported current substance use, efforts to mitigate the consequences of trauma exposure should include screening, brief interventions, and referral to treatment for substance use.…”
Section: Discussionmentioning
confidence: 97%
“… 3 , 4 Alcohol and other drug use may exacerbate the effect of gender power imbalances and IPV on HIV risk. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Another major finding was that participants who had experienced recent violence by their main sexual partner were significantly more likely to exhibit verbal and physical aggression. This is not altogether surprising, since research has found that substance-using women in the Western Cape are at increased risk of interpersonal violence [ 10 ]. It is possible that being the victim of intimate partner violence may result in women becoming aggressive and violent themselves [ 16 ] if this trauma is left untreated.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high prevalence of violence against women in some communities in the Western Cape. including among substance-using women whom studies have shown are especially vulnerable to interpersonal violence [ 10 , 11 ]. While traditionally men who engage in this type of violence have often witnessed it in their childhood and therefore hold traditional views on gender-norms, such gender-disparities in violence perpetration are likely to shift as traditional gender roles in South Africa evolve [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%